Effectiveness of pancreatic stent placement in pediatric patients with acute recurrent and chronic pancreatitis - Gerardo Blanco-Rodriguez; Mallerli N. Ledezma-Cifuentes; Eustorgio S. García-Cárdenas; Gerardo Blanco-Velasco; Mario Peña-García; Jaime Penchyna-Grub; Gustavo Teyssier-Morales; Jessie N. Zurita-Cruz (Boletín Médico del Hospital Infantil de México, 2023)
Background: The use of pancreatic prostheses in children with acute recurrent pancreatitis (ARP) and chronic pancreatitis (CP) has evolved. The main established indication is the treatment of persistent abdominal pain. This study aimed to evaluate the efficacy of pancreatic stenting for refractory abdominal pain in pediatric patients with ARP and CP. Methods: We conducted a retrospective case series study. We included patients under 16 years of age diagnosed with ARP and CP in the study. Endoscopic retrograde cholangiopancreatography (ERCP) was performed with the insertion of one and later two pancreatic stents. We evaluated abdominal symptoms before and after treatment, number of changes, duration of treatment, and complications with follow-up at 24 months and after withdrawal. Results: Nine patients with ARP and CP were included in the study: six with undetermined etiology and three with pancreas divisum. The mean age was 12.4 years. Prosthesis placement relieved abdominal pain in 100% of cases, with 3.2 replacement sessions every 6.2 months for 27.4 months, and mild complications (15.7%). One patient experienced pain on removal of the prosthesis and required bypass surgery. Conclusion: Pancreatic stent placement in patients with refractory abdominal pain with ARP and CP proved to be effective and safe, providing medium-term symptom relief and minimal complications.